Spacecraft for Hypervelocity Impact Research – An Overview of Capabilities, Constraints and the Challenges of Getting There. (2015) - Grundmann, Jan Thimo; Dachwald, Bernd; Grimm, Christian D.; Kahle, Ralph; Koch, Aaron Dexter; Krause, Christian; Lange, Caroline; Quantius, Dominik; Ulamec, Stephan
Abstract: We present an introductory overview of the capabilities, constraints and challenges to be taken into account in the design of space missions for HVI research and application, focusing on related planetary defence applications, small spacecraft approaches, using our activities and projects as examples. Large lightweight deployable structure applications are discussed, for large-scale photovoltaic arrays in advanced solar-electric propulsion missions, and for solar sailing as a non-fuel-constrained method of achieving high-energy or retrograde orbit and multiple target missions. Small asteroid landers are discussed as vehicles for precursor exploration of impact target asteroids, precision target orbit determination, and for impact process monitoring that also can be deployed from sail-based missions.